The Potential and the Limitations of Esophageal Robotic Surgery in Children - Ferrero, Pierre Alexandre; Blanc, Thomas; Binet, Aurélien; Arnaud, Alexis; Abbo, Olivier; Vatta, Fabrizio; Bonnard, Arnaud; Spampinato, Grazia; Lardy, Hubert; Fourcade, Laurent; Ballouhey, Quentin (European Journal of Pediatric Surgery, 2020)
Introduction There have been numerous reports of robotic pediatric surgery in the literature, particularly regarding urological procedures for school-aged children. Thoracic procedures appear to be less common, despite the fact that encouraging results were reported more than 10 years. Our aim was to report a national experience of esophageal robotic-assisted thoracoscopic surgery (ERATS) and to discuss the most appropriate indications.Materials and Methods A retrospective multicenter study was conducted to compile the ERATS performed at five French surgical centers that have been involved in spearheading robotic pediatric surgery over the past 15 years. The data were supplemented by a review of the literature.Results Over the study period, 68 cases of robotic thoracic surgery were performed at the five pediatric centers in question. ERATS was performed for 18 patients (mean age 7.1 years [ ± 5.6]) in four of the centers. These comprised seven esophageal duplications, four esophageal atresias, five Heller's myotomies, and two cases of esophagoplasty. A conversion was needed for two neonates (11%) due to exposure difficulties. Four other procedures for patients who weighed less than 15 kg were successfully completed without causing postoperative complications. In the past 12 years, 22 other cases of ERATS were published worldwide. The indications were the same, except for esophagoplasty, which was not found.Conclusion Aside from accessibility issues with the robotic platform, the main limitation is still very much that the low body weight of children results in incompatibility between the size of the trocars and the size of the intercostal space. ERATS is clearly a feasible procedure with technical advantages for most pediatric cases with body weights more than 15 kg. A transdiaphragmatic abdominal approach should be considered for lower esophagus surgery.
Keywords: esophagus; robotic surgery; pediatric